KECERDASAN EMOSI DAN IMPULSE BUYING ONLINE PADA ANGGOTA FORUM KASKUS DI YOGYAKARTA - Akbar Amada Putra; Rumiani Rumiani (UIN Sunan Kalijaga, 2013)
This study aims to examine corelation between emotional quotient and online impulse buying on member of Kaskus forum in Yogyakata region. The subjects of this research were Kaskus member who have any transaction or did online shopping via Kaskus and lives in Yogyakarta. The data were collected using emotional quotient scales from Goleman theory (1999) and Impulse buying online scale from Mesiranta theory (2009). The result of analyze showed that emotional quotient was a very correlated to impulse buying online with level r valkeceue -0.433with p = 0.005 (p < 0.05) Based on this fnding, the hypothesis was accepted.